2015
DOI: 10.1007/s12026-015-8669-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of complement activation in atherogenesis: the first 40 years

Abstract: The pathogenesis of atherosclerotic inflammation is a multi-step process defined by the interweaving of excess modified lipid particles, monocyte-macrophages populations, and innate immune and adaptive immunity effectors. A part of innate immunity, the complement system, is an important player in the induction and progression of atherosclerosis. The accumulation of either oxidized or enzymatically modified LDL-bound to C-reactive protein or not-prompts complement activation leading to the assembly of the termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 122 publications
0
47
0
Order By: Relevance
“…4). Overactivation of the complement pathway has been implicated in plaque development and destabilization [44,45]. Complement activation also influences thrombosis through activation of platelets, promotion of fibrin formation, and impairment of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…4). Overactivation of the complement pathway has been implicated in plaque development and destabilization [44,45]. Complement activation also influences thrombosis through activation of platelets, promotion of fibrin formation, and impairment of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, it has been demonstrated that free cholesterol activates complement (52) and since then, several reviews summarized the evidence for an important impact of complement activation on atherogenesis (53)(54)(55)(56). Thereby, an unexpectedly large number of pathways are operative that may differentially influence the evolution of the atherosclerotic lesion.…”
Section: Complement Activationmentioning
confidence: 99%
“…Conversely, DI Franco et al[ 104 ] found no significant difference in QTc interval duration amongst CIA patients treated with TNFi and rituximab. However, the authors did not report on disease activity and thus there may be have been a large proportion of patients who did not achieve adequate disease control[ 105 ]. In the Diana study, 12 wk of treatment with combination synthetic DMARDs or biologics significantly improved cardiac autonomic dysfunction ( P < 0.05) in both RA and AS patients[ 106 ].…”
Section: Impact Of Disease-modifying Anti-rheumatic Drugs and Biologimentioning
confidence: 99%
“…However, the use of biologics is not without risk, and beyond the well-recognized risks of malignancy and infection, there have been reports of cardiac arrhythmias, in some cases life threatening, particularly following the use of anti-TNF monoclonal antibodies and rituximab[ 105 ]. Case reports have described ventricular arrhythmias[ 108 , 109 ], supraventricular arrhythmias[ 110 , 111 ], and various degrees of heart block[ 112 - 114 ], associated with the use of infliximab, although in one case, the complete heart block did in fact resolve spontaneously[ 112 ].…”
Section: Impact Of Disease-modifying Anti-rheumatic Drugs and Biologimentioning
confidence: 99%
See 1 more Smart Citation